Seismic stratigraphy of a partially filled incised valley on a semi-arid continental shelf, Northeast Brazil - Ximenes Neto, Antonio Rodrigues (2021)
This study aimed to understand the key surfaces and the sedimentary filling pattern of the Coreaú incised valley (CIV) system (NE Brazil) using high-resolution seismic stratigraphy. Six key surfaces (Ss) and five seismic units (SUs) were identified. The difference in the basal reflector (S1) and the paleointerfluve (modern sea floor) was verified to be up to 40 m of incision, of which only 20 m are filled. S1 (sequence boundary—SB) was associated with the acoustic basement (Tibau Formation/Barreiras Group) and presented strong control (antecedent topography) in the incision (re-incisions in the Pleistocene lowstands) and sedimentary stacking pattern. The CIV fill showed lowstand system tract, LST (chaotic facies)–transgressive system tract, TST (horizontal layers to chaotic facies)–highstand system tract, HST (chaotic facies) from the base to top. Thin fluvial deposits above SB correspond to LST. Overlapping this system tract is the first marine flooding surface—transgressive surface. Afterwards, the largest seismic unit (lateral and vertical) with sub-parallel and parallel (onlap) seismic facies, interpreted as related to a low energy system, with shallow gas, and vertical accretion (central basin of estuary) occurred. This environment is related to the drowning of the shelf from the shelf break (a decrease in gradient). A tide ravinement surface truncated the top of SU3 and favored coastal to shallow marine deposition. The transgressive system tract (TST) is thicker in the middle (mainly) and outer sectors in the fluvial troughs (depocenter). The maximum flooding surface appears near the sea floor and favored the development above of carbonate sedimentation in the HST. These seimostratigraphic stacking patterns showed a strong influence of semi-arid climate and antecedent topography/structural inheritance. Thus, it is evident that the filling of the CIV differs from other valleys on semiarid systems and/or influenced by paleotopography (e.g., South Africa and Texas Shelf), which demonstrates the importance of local settings. The great influence of estuarine to coastal sediments in the valley infilling is also observed in the modern Coreaú coastal plain incised valley.